The repatriation of Yagan : a story of manufacturing dissent - H. McGlade (Law Text Culture, 1998)
kaya yarn nyungar gnarn wangitch gnarn noort balaj goon kaart malaam moonditj listen Nyungars, I tell you, our people, our brother he come home, we lay his head down ... Old Nyungar men are singing, and the clapping sticks can be heard throughout Perth's international airport late in the night. There are up to three hundred Nyungars who have come to meet the Aboriginal delegation due to arrive on the 11pm flight from London. The delegation are bringing home the head of Yagan, the Nyungar warrior.